Idea of the Soul in the Japanese and Russian Lingvocultures - D. A. Tatarskaya (Vestnik MGIMO-Universiteta)
The article is devoted to the comparison of Japanese and Russian idea of soul. It touches upon the subject of the place of this concept in the system of values of Japanese and Russian. The author gives a number of arguments for the fact that there is some similarity between Japanese and Russian views on the soul.